Flattening filter free beams from TrueBeam and Versa HD units: Evaluation of the parameters for quality assurance. Issue 1 (23rd December 2015) - Fogliata, Antonella; Fleckenstein, Jens; Schneider, Frank; Pachoud, Marc; Ghandour, Sarah; Krauss, Harald; Reggiori, Giacomo; Stravato, Antonella; Lohr, Frank; Scorsetti, Marta; Cozzi, Luca
Abstract : Purpose: Flattening filter free (FFF) beams generated by medical linear accelerators are today clinically used for stereotactical and non‐stereotactical radiotherapy treatments. Such beams differ from the standard flattened beams (FF) in the high dose rate and the profile shape peaked on the beam central axis. Definition of new parameters as unflatness and slope for FFF beams has been proposed based on a renormalization factor for FFF profiles. The present study aims to assess the dosimetric differences between FFF beams generated by linear accelerators from different vendors, and to provide renormalization and parameter data of the two kinds of units. Methods: Dosimetric data from two Varian TrueBeam and two Elekta Versa HD linear accelerators, all with 6 and 10 MV nominal accelerating potentials, FF and FFF modes have been collected. Renormalization factors and related fit parameters according to Fogliata et al. ["Definition of parameters for quality assurance of flattening filter free (FFF) photon beams in radiation therapy, " Med. Phys.39, 6455–6464 (2012)] have been evaluated for FFF beams of both units and energies. Unflatness and slope parameters from profile curves were evaluated. Dosimetric differences in terms of beam penetration and near‐the‐surface dose were also assessed. Results: FFF profile parameters have been updated; renormalization factors and unflatness from the Varian units are consistent with the published data. Elekta FFF beam qualities, different from the Varian generated beams, tend to express similar behaviour as the FF beam of the corresponding nominal energy. TPR20, 10 for 6 and 10 MV FF and FFF TrueBeam beams are 0.665, 0.629 (6 MV) and 0.738, 0.703 (10 MV). The same figures for Versa HD units are 0.684, 0.678 (6 MV) and 0.734, 0.721 (10 MV). Conclusions: Renormalization factor and unflatness parameters evaluated from Varian and Elekta FFF beams are provided, in particular renormalization factors table and fit parameters.